Advances in computers, volume 67, Web technology ([S.l.] : Elsevier Academic Press, 2006)
This volume is number 67 in the series Advances in Computers that began back in 1960. This is the longest continuously published series of books that chronicles the evolution of the computer industry. Each year three volumes are produced presenting approximately 20 chapters that describe the latest technology in the use of computers today. Volume 67, subtitled "Web technology," presents 6 chapters that show the impact that the World Wide Web is having on our society today. The general theme running throughout the volume is the ubiquity of web services. Topics such as wireless access and its problems and reliability of web communications are emphasized. Key features: - In-depth surveys and tutorials on software development approaches. - Well-known authors and researchers in the field. - Extensive bibliographies with most chapters. - All chapters focus on Internet and web technology issues. - Discussion of wireless communication and forensic issues, currently important research areas. - In-depth surveys and tutorials on software development approaches. - Well-known authors and researchers in the field. - Extensive bibliographies with most chapters. - All chapters focus on Internet and web technology issues. - Discussion of wireless communication and forensic issues, currently important research areas.
Preface. -- Contributors. -- Chapter 1. Broadcasting a Means to Disseminate Public Data in a Wireless Environment -- Issues and Solutions (A.R. Hurson, Y. Jiao and B.A. Shirazi). -- Chapter 2. Programming Models and Synchronization Techniques for Disconnected Business Applications (A. Leff and J.T. Rayfield). -- Chapter 3. Academic Electronic Journals: Past, Present and Future (A. Hovav and P. Gray). -- Chapter 4. Web Testing for Reliability Improvement (J. Tian and L. Ma). -- Chapter 5. Wireless Insecurities (M. Sthultz, J. Uecker and H. Berghel). -- Chapter 6. The State of the Art in Digital Forensics (D. Forte).
Keywords: World Wide Web; Computer software -- Development; User interfaces (computer systems).; Electronic books